BIOPROSPEKSI TUMBUHAN OBAT HUTAN SEBAGAI SUMBER SENYAWA ANTIMIKROBA - Hafizah Nahlunnisa (LPPM Universitas Muhammadiyah Jambi, 2026)
Indonesia's tropical forests are a source of diverse medicinal plants with potential bioactive compounds, particularly antimicrobial agents. Bioprospecting is a systematic approach to exploring and utilizing these biological resources to discover compounds with pharmacological value. This article reviews the bioprospecting of forest medicinal plants as sources of antimicrobial compounds, focusing on secondary metabolites such as alkaloids, flavonoids, tannins, terpenoids, and essential oils. Several plant species found in tropical forests including Azadirachta indica (neem), Curcuma aeruginosa (black turmeric), Zingiber officinale (ginger), Rhizophora mucronata (bakau), and various wetland plants have demonstrated significant antimicrobial activity against pathogenic bacteria and fungi such as Staphylococcus aureus, Escherichia coli, and Candida albicans. These findings highlight the importance of integrating ethnopharmacological knowledge with modern phytochemical and microbiological methods. Sustainable bioprospecting practices, supported by appropriate regulatory frameworks, are essential for the conservation and equitable utilization of forest biodiversity as a source of future antimicrobial drugs.